2020
DOI: 10.1080/10130950.2019.1704485
|View full text |Cite
|
Sign up to set email alerts
|

An examination of social media as a platform for cyber-violence against the LGBT+ population

Abstract: The popularity of social media raises concerns related to cyber-violence and the security of marginalised individuals and groups, including the lesbian, gay, bisexual and transgender (LGBT+) population. Developing worthy interventions requires exploration of the LGBT+ population's experiences of cyber-violence in relation to gender discrimination, which was the aim of this study. A qualitative approach sourced data between 2017 and 2019 from LGBT+ Facebook groups and pages and semi-structured interviews with p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 18 publications
0
8
0
1
Order By: Relevance
“…Sabinet Law (2017) states that South African legislation is in the process of being amended to deal with emerging cyberspace intimidation, as evidenced in the tabling of the Cybercrimes and Cybersecurity Bill. Cyberbullying is more likely to fall under harassment or bullying (Sacco et al, 2012:5), as in the case of South Africa (Mkhize et al, 2020). If a cyberbullying incident is not reported to the appropriate authorities, a single post may be accessible for many years after the incident takes place, leading to long-term abuse of the victim(s) due to the permanency associated with the post (Wolak et al, 2007).…”
Section: The Impact Of Cyber Bullying On Victimized Youth and Childrenmentioning
confidence: 99%
“…Sabinet Law (2017) states that South African legislation is in the process of being amended to deal with emerging cyberspace intimidation, as evidenced in the tabling of the Cybercrimes and Cybersecurity Bill. Cyberbullying is more likely to fall under harassment or bullying (Sacco et al, 2012:5), as in the case of South Africa (Mkhize et al, 2020). If a cyberbullying incident is not reported to the appropriate authorities, a single post may be accessible for many years after the incident takes place, leading to long-term abuse of the victim(s) due to the permanency associated with the post (Wolak et al, 2007).…”
Section: The Impact Of Cyber Bullying On Victimized Youth and Childrenmentioning
confidence: 99%
“…A recent study by Mkhize et al (2020) probed into the cyber violence experienced by sexual minority individuals on Facebook and found that they were frequently exposed to heterosexist memes, pictures, and written comments on personal timelines and public pages. The comments showing hatred toward homosexuality were also posted through creating fake accounts and getting into lesbian, gay, bisexual, transgender, and queer (LGBTQ) groups, insulting and threatening the members in the group (Mkhize et al, 2020). This type of cyber violence infiltrates the space created for LGBTQ individuals, and possibly increases their exposure to online victimization.…”
Section: Introductionmentioning
confidence: 99%
“…This does not negate the fact that social media spaces can be hostile towards LGBTQ+ people. LGBTQ+ people report experiencing online hate-speech, trolling, harassment and threats of sexual and physical violence (Mkhize et al, 2020; Scheuerman et al, 2018). Consequently, many LGBTQ+ people carefully manage their performances of gender and sexuality on social media (Hanckel et al, 2019).…”
Section: Introductionmentioning
confidence: 99%